Dazomet fumigation modification of the soil microorganism community and promotion of Panax notoginseng growth - Lin, Ya-meng; Li, Ming-hua; Dai, Chun-yan; Liu, Yuan; Zhang, Wen-ping; Yang, Qian; Cui, Xiu-ming; Yang, Ye (Frontiers in Microbiology, 2024)
Panax notoginseng, a medicinal herb in China, is attacked by several pathogens during its cultivation. Dazomet (DZ) is a soil fumigant that is effective in controlling soil-borne pathogens, but its long-term effects on P. notoginseng growth and soil properties are unknown. We conducted field experiments over two consecutive years to assess the impact of three concentrations of DZ fumigation (35 kg/666.7 m2, 40 kg/666.7 m2, and 45 kg/666.7 m2) on soil physicochemical properties, microbial diversity, and P. notoginseng growth. Correlation analyses were performed between microbial community changes and soil properties, and functional predictions for soil microorganisms were conducted. DZ fumigation increased total nitrogen, total phosphorus, total potassium, available phosphorus, available potassium, and ammonia nitrogen levels in the soil. DZ fumigation promoted the nutrient accumulation and improvement of agronomic traits of P. notoginseng, resulted in a 2.83–3.81X yield increase, with the highest total saponin content increasing by 24.06%. And the 40 kg/666.7 m2 treatment had the most favorable impact on P. notoginseng growth and saponin accumulation. After DZ fumigation, there was a decrease in the relative abundance of pathogenic fungi such as Fusarium, Plectosphaerella and Ilyonectria, while beneficial bacteria such as Ramlibacter, Burkholderia, and Rhodanobacteria increased. The effects of fumigation on soil microorganisms and soil physicochemical properties persisted for 18 months post-fumigation. DZ fumigation enhanced the relative abundance of bacteria involved in the biosynthesis of secondary metabolites and arbuscular mycorrhizal fungi, reduced the relative abundance of plant-animal pathogenic fungi, reduced the occurrence of soil-borne diseases. In conclusion, DZ fumigation enhanced soil physicochemical properties, increased the proportion of beneficial bacteria in the soil, and rebalanced soil microorganism populations, consequently improving the growth environment of P. notoginseng and enhancing its growth, yield, and quality. This study offers a theoretical foundation for DZ fumigation as a potential solution to the continuous cropping issue in perennial medicinal plants such as P. notoginseng.